Metodyka sporządzania ocen stanu technicznego obwałowań przeciwpowodziowych z zastosowaniem badań nieinwazyjnych = Methodology of preparing the estimates of technical condition of flood-control embankments with the use of non-invasive methods - Reszka, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In 1994, the Technical Deparlment for Dam Control of the Institute of Meteorology and Water Management - Krakow Branch - with the seat in Dobczyce worked out several recommendations referring to the way of estimating the technical condition of embankments and their base. Non-invasive geological examinations, including electromagnetic and multi channel radar cross-sectioning were recommended as basic ones. The results of these examinations were used to determine places in which site geophysical estimations were to be performed (test bore-holes, sounding, sampling) as well as their scope.
Keywords: 2 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: zagospodarowanie zlewni" (21-22.06.2001)